Strategi Sekolah Adat Pesinauan dalam upaya pemertahanan Adat dan Budaya Osing desa Olehsari Kec. Glagah Kab.Banyuwangi - Yans Alloydia Putri Hanatika; Indar Sabri (Yayasan Pendidikan Penelitian Pengabdian Algero, 2026)
This study aims to describe and analyze the strategies implemented by the Sekolah Adat Pesinauan in preserving the customs and culture of the Osing community in Olehsari Village, Glagah Subdistrict, Banyuwangi District. The background of this research stems from concerns about the erosion of local cultural values due to the strong influence of modernization and globalization. The research method employed is qualitative with a descriptive approach. Data were collected through observation, in-depth interviews with school administrators, community leaders, and documentation of culture-based learning activities. The results show that Sekolah Adat Pesinauan plays a strategic role in preserving Osing culture through various programs such as Osing language learning, traditional arts (such as gandrung, barong, and hadrah kuno), and the strengthening of customary values in daily life. The strategies include the integration of culture-based education, community empowerment, and collaboration with formal educational institutions. These efforts have successfully fostered youth awareness of the importance of preserving local cultural heritage. In conclusion, Sekolah Adat Pesinauan serves as an effective model for community-based cultural preservation in the modern era.